Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1111/1756-185x.12579
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patients with ankylosing spondylitis (AS) and non‐radiographic axial spondyloarthritis (nr‐axSpA) from a single rheumatology clinic in New Delhi

Abstract: Aim: Comparison of ankylosing spondylitis (AS) with non-radiographic axial spondyloarthritis (nr-axSpA) classified with the recent ASsessment of spondyloArthritis International Society (ASAS) criteria. Patients & Methods:This study included 288 patients clinically diagnosed as having spondyloarthritis (SpA) where a satisfactory radiograph of sacroiliac (S-I) joints was available. The AS and the nr-axSpA groups were compared for the various SpA-related variables.Results: Of 288 axSpA patients, there were 187 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 25 publications
(57 reference statements)
6
16
1
Order By: Relevance
“…Our findings were consistent with those of previously published clinical trials and observational studies from outside of the US, which showed that despite some differences in patient and clinical characteristics, patients with nonradiographic axial SpA and those with AS were mostly similar and shared significant disease burden . In the current study, patients with nonradiographic axial SpA were younger, more often had enthesitis, and had better spinal mobility; however, the percentages of patients with presenteeism and overall activity impairment were significantly greater among those with nonradiographic axial SpA compared with those with AS.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings were consistent with those of previously published clinical trials and observational studies from outside of the US, which showed that despite some differences in patient and clinical characteristics, patients with nonradiographic axial SpA and those with AS were mostly similar and shared significant disease burden . In the current study, patients with nonradiographic axial SpA were younger, more often had enthesitis, and had better spinal mobility; however, the percentages of patients with presenteeism and overall activity impairment were significantly greater among those with nonradiographic axial SpA compared with those with AS.…”
Section: Discussionsupporting
confidence: 92%
“…This study of patients from the Corrona PsA/SpA Registry represents one of the first national‐level analyses of patients with nonradiographic axial SpA and patients with AS from multiple geographic regions and a mix of primary and tertiary clinical centers across the US. Although the criteria for classification of nonradiographic axial SpA were established in 2009 , patients with nonradiographic axial SpA have been described in only a limited number of clinical trials, registry reports, and observational studies, most of which were conducted outside of the US . In clinical trial settings, patients with nonradiographic axial SpA were typically defined as those who met the ASAS classification criteria for axial SpA but did not meet the radiology criterion of the 1984 modified New York criteria for AS, similar to the definition used in the current analysis .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In several cross-sectional studies comparing patients with nonradiographic axial SpA to patients with AS, a notable finding has been a higher proportion of men with AS as compared to nonradiographic axial SpA (3,8,9,14). Men were also found to have a higher likelihood of sacroiliitis on MRI (20).…”
Section: Discussionmentioning
confidence: 99%